Hero. (Pasig City : Viva Video, 2002)
During the violent unification of China's warring states that resulted in the establishment of the Qin dynasty, assassins undertake the monumental task of confronting the King of Qin, China's first emperor, who has resisted a decade's worth of attempts on his life.